3y-18x=12

Simple and best practice solution for 3y-18x=12 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3y-18x=12 equation:


Simplifying
3y + -18x = 12

Reorder the terms:
-18x + 3y = 12

Solving
-18x + 3y = 12

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-3y' to each side of the equation.
-18x + 3y + -3y = 12 + -3y

Combine like terms: 3y + -3y = 0
-18x + 0 = 12 + -3y
-18x = 12 + -3y

Divide each side by '-18'.
x = -0.6666666667 + 0.1666666667y

Simplifying
x = -0.6666666667 + 0.1666666667y

See similar equations:

| -5(8q+2)= | | -3n-2+7n=-4+2+6n-2n | | x^2+1=2 | | 7(2-3b)+4=-34-8b | | 2(3+4m)=4+3m | | 3G+3(-3+2g)=1-g | | 9-4x=24 | | x+2=-7+x+7 | | 7x+24=x | | 2x^3-x^2-15x= | | 6x+6x=-14+6x+8x | | 2(k+4)=3(k-2) | | 79-6x=39x+19 | | 3*x+1=7*x-11 | | m-7-3=-6+m+2-3m | | 13-7x=208-42x | | 3r-10=2r-3 | | 7-x=-x+7 | | 2a+4b+a-b= | | y=7+3x+0.5x^2 | | y=4-3*-3 | | P+4p=p+3p-3 | | 18=2(x+3) | | x^2+7x-32=0 | | 2(y-4)=-4+10 | | 6b-3+b=2b+12 | | 66-3x=42x+16 | | 0.5x+8=14 | | 12=2(x+3) | | (-3x*3+4)(7x-2)= | | 8-10x=58-45x | | 15+0.4x-0.05x^2=0 |

Equations solver categories